2019
DOI: 10.23947/1992-5980-2019-19-2-104-112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic properties of interacting subsystems on evolution of selective transfer formation in friction units

Abstract: Заковоротный В. Л. и др. Влияние динамических свойств взаимодействующих подсистем на эволюцию Zakovorotny V. L. et al.. Effect of dynamic properties of interacting subsystems on evolution of selective transfer formation in friction units

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our studies aimed at forming wear-free friction conditions have shown that the selective transfer may not be formed in friction of steel-bronze in glycerol in depend on the dynamic parameters of the indenter [37], [38]. There is other, as a rule, experimental studies aimed at revealing the connection of dynamics and wear resistance of friction units [15]- [19].…”
Section: Fig 4 Examples Of Trajectories In Phase Space Sections Depending On the Work Done By Friction Forcesmentioning
confidence: 96%
See 1 more Smart Citation
“…Our studies aimed at forming wear-free friction conditions have shown that the selective transfer may not be formed in friction of steel-bronze in glycerol in depend on the dynamic parameters of the indenter [37], [38]. There is other, as a rule, experimental studies aimed at revealing the connection of dynamics and wear resistance of friction units [15]- [19].…”
Section: Fig 4 Examples Of Trajectories In Phase Space Sections Depending On the Work Done By Friction Forcesmentioning
confidence: 96%
“…Therefore, as surfaces come closer, first, the forces of contact interaction increase and, second, normal and tangential forces are redistributed. Their thorough analysis shows that in certain cases there are potential barriers in these characteristics associated with various physical phenomena, for example, the destruction of the servovite film (protective tribofilm) [10], [37], [38]. Let us call changes in contact interaction forces caused by surfaces coming closer together approximation functions.…”
Section: Example Of the System And Its Propertiesmentioning
confidence: 99%